2023
DOI: 10.1021/acsomega.2c07128
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Sericin-Tagged Layered Double Hydroxides for Combined Delivery of Pemetrexed and ZnO Quantum Dots as Biocompatible Cancer Nanotheranostics

Abstract: Aim: Despite extensive progress in the field of cancer nanotheranostics, clinical development of biocompatible theranostic nanomedicine remains a formidable challenge. Herein, we engineered biocompatible silk-sericin-tagged inorganic nanohybrids for efficient treatment and imaging of cancer cells. The developed nanocarriers are anticipated to overcome the premature release of the chemotherapeutic drug pemetrexed (PMX), enhance the colloidal stability of layered double hydroxides (LDHs), and maintain the lumine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 78 publications
0
1
0
Order By: Relevance
“…pH‐sensitive ZnO QDs have shown potential for drug delivery applications, especially in targeting cancer cells. Previous reports suggested that drug‐loaded ZnO QDs nanoformulation efficiently delivers the drug and mediates the apoptosis against different cancers by using its acidic pH 36–38 . In previous research, it was stated that ZnO QDs were observed at the 360 nm UV spectral peak 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pH‐sensitive ZnO QDs have shown potential for drug delivery applications, especially in targeting cancer cells. Previous reports suggested that drug‐loaded ZnO QDs nanoformulation efficiently delivers the drug and mediates the apoptosis against different cancers by using its acidic pH 36–38 . In previous research, it was stated that ZnO QDs were observed at the 360 nm UV spectral peak 39 .…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory concentration (IC 50 and IC 90 ) of CVC-ZnO QDs was measured to be 20.47 ± 0.54 µg/mL and 78.28 ± 0.67 µg/mL, cancers by using its acidic pH. [36][37][38] In previous research, it was stated that ZnO QDs were observed at the 360 nm UV spectral peak. 39 The UV spectrum of the CVC-ZnO QDs obtained in this investigation was in perfect accord with it.…”
Section: Effect Of Cvc-zno Qds On the Mda-mb-231 Cell Survivalmentioning
confidence: 99%
“…The results of this study suggest that although the presence of the amino acids did not significantly improve transfection efficiency compared to non-functionalized LDHs, histidine functionalization of the gene delivery vehicle resulted in better transfection than arginine functionalization. Overall, it has been proposed that the ease of loading, anionic exchangeability, and biocompatibility have opened up the avenue for using LDHs as delivery agents in cancer therapy [67].…”
Section: Discussionmentioning
confidence: 99%
“…QDs, due to their small particle size, good dispersibility, and excellent biocompatibility, are widely used as drug carrier materials in tumor treatment. It has been reported that QDs can promote the release of various drugs, such as doxorubicin (Figure 6) [103][104][105][106][107][108], paclitaxel [109,110], pemetrexed [111], 5-fluorouracil [112], etc. The use of a single QD carrier in vivo is desirable, as carriers of a moderate size (approximately 10 to 20 nm in diameter) can reduce the reticuloendothelial system uptake and renal clearance rate of drugs, thereby increasing the circulation time in the blood and improving the delivery efficiency [113].…”
Section: Chemotherapymentioning
confidence: 99%
“…Non-functionalized modified QDs Chemotherapy QDs carry doxorubicin [103][104][105][106][107][108] Breast cancer Lung cancer Cervical cancer Hepatocarcinoma Glioblastoma QDs carry paclitaxel [109,110] Hepatocarcinoma Prostate cancer QDs carry pemetrexed [111] Breast cancer QDs carry 5-fluorouracil [112] Lung cancer PTT/PDT CdSe/ZnS QDs [120] Pancreatic cancer MoSe2 NDs [121] Cervical cancer Cu-Sec QDs [122] Hepatocarcinoma DPP-CTS-CQDs [124] Hepatocarcinoma CNQD-CN [127] Cervical cancer…”
Section: Modification Of Qds Modalities Of Treatment Qds Types Of Cancermentioning
confidence: 99%